Kompas Group’s Dual-Product Strategy in Indonesia’s Digital Media Economy: A Picardian Media Economics Analysis - Anita Dwi Zulyatin; Muhammad Arifin Ilham; Primo Thoriq Qodri; Nurhaliza Putri Arifianti (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
This study addresses the challenge legacy media face in sustaining economic viability amid digital disruption in Indonesia, focusing on the tension between journalistic idealism and business sustainability. The objective of this research is to examine the economic strategies Kompas Group employs to manage the dual-product media market amid intensified competition and changing audience behavior. This study applies a descriptive qualitative research method, with data collected through in-depth interviews with a media economics expert, internal representatives of Kompas Group, and Generation Z audiences, supported by a literature review and secondary data analysis. The findings indicate that Kompas Group implements a dual economic strategy by separating advertising-driven platforms, such as Kompas.com, from subscription-based digital journalism through Kompas.id. Although this strategy demonstrates adaptive efforts toward digital transformation, its effectiveness remains constrained by structural challenges, including declining advertising revenues, low willingness among younger audiences to pay for news, reduced tolerance for digital advertising, and weakened brand loyalty due to algorithm-driven news consumption on social media. Additionally, both intramedia competition with digital-native media and intermedia competition with global technology platforms further intensify economic pressures on legacy media. This study concludes that the long-term sustainability of Kompas Group depends not only on technological innovation but also on its capacity to adapt to evolving audience behavior, address structural imbalances in the digital media economy, and diversify revenue sources while maintaining core journalistic values.